Literature Rivew: Effectiveness of Speech Therapy in Improving Verbal Communication Ability of Stroke Patients with Dysarthria” - Eko Kurniawan; Suyanto Suyanto; Erna Melastuti; Dwi Retno Sulistyaningsih (Indonesian Journal of Global Health Research, 2025)
Stroke often results in speech impairment, including dysarthria, which impacts the patient's verbal communication skills, quality of life, social interaction and independence. Therefore, understanding the effectiveness of speech therapy in improving verbal communication skills is necessary to determine the most effective rehabilitation approach. Objective: This study aims to explore the effectiveness of speech therapy in improving verbal communication of stroke patients with dysarthria, particularly in the aspects of articulation, voice clarity, and the ability to speak in daily life. Method: Methods: This study used a literature review of national and international published between 2019-2024 and freely available. A systematic search of the review was conducted using the Google Scholar database, Semantic Scholar, using keywords: Dysarthria Speech Therapy, Stroke, using the PCC (Population, Concept, Context) approach. The article selection process used PRISMA which was then subjected to critical appraisal. Initial searches were conducted through Google Scholar (1,215 articles), Semantic Scholar (485 articles). Initial screening of 1,450, removal of duplicate articles remaining 250 articles, articles were eliminated, so only 15 articles entered the further screening stage. From this process, 5 articles did not meet the criteria and were excluded. Finally, 10 articles that met the inclusion criteria were selected and reviewed.. Result: The results of thousands of articles show ten articles showing consistent results that speech therapy can improve verbal communication skills in patients with diarthric stroke. Conclusion: There is general agreement that speech therapy is effective in improving verbal communication skills in stroke patients with dysarthria.